2015
DOI: 10.1002/acn3.227
|View full text |Cite
|
Sign up to set email alerts
|

Neurocognitive decline in HIV patients is associated with ongoing T‐cell activation in the cerebrospinal fluid

Abstract: ObjectiveHIV-associated neurocognitive disorders (HAND) remain a challenge despite combination antiretroviral therapy (cART). Immune cell activation has been implicated to play a major role in the development of HAND.MethodsIn this study, we used multicolor flow cytometry on peripheral blood (PB) and cerebrospinal fluid (CSF) samples to determine the expression of HLA-DR and programmed death-1 (PD-1) on CD4+ and CD8+ T cells in patients with chronic HIV infection. Expression levels were correlated with HI viru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
24
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 49 publications
3
24
1
Order By: Relevance
“…38 Both studies suggested that immune activation may actually provide a neuroprotective effect in the pediatric population. This is in stark contrast to the data in the adult population that shows deleterious effects of immune activation on the CNS 3941 . Both pediatric studies evaluated relatively young children (median age 6–7 years) with perinatal HIV who had only been on cART for a relatively short period of time or who were not on therapy.…”
Section: Discussioncontrasting
confidence: 99%
“…38 Both studies suggested that immune activation may actually provide a neuroprotective effect in the pediatric population. This is in stark contrast to the data in the adult population that shows deleterious effects of immune activation on the CNS 3941 . Both pediatric studies evaluated relatively young children (median age 6–7 years) with perinatal HIV who had only been on cART for a relatively short period of time or who were not on therapy.…”
Section: Discussioncontrasting
confidence: 99%
“…[32] While most of the literature has focused on monocyte associations with HAND, it is well recognized that activated lymphocytes can enter and leave the brain, and the contributions of CD8+ T cells producing interferon gamma have recently been associated with HAND as well. [33,34]…”
Section: Biomarkers and Handmentioning
confidence: 99%
“…Recent work demonstrates that percentage of CD8+ T lymphocytes in CSF, and in particular those that express interferon gamma, positively associate with the presence of HAND even in individuals on virologically successful cART [61]. In an independent study of participants mostly on suppressive cART, increased markers of CSF CD4+ CD8+ T lymphocyte activation and exhaustion correlated with poorer performance on neuropsychological testing and periventricular brain imaging abnormalities suggestive of inflammation [62]. These studies suggest a pathologic role of CNS lymphocyte activation that persists despite cART.…”
Section: Immune Cells and Tissues Involved In Pathogenesismentioning
confidence: 99%